Farmer participatory variety selection (PVS) as part of enhancing groundnut productivity and production - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Farmer participatory variety selection (PVS) of 39 improved groundnut varieties resulted in the selection of 17 varieties having traits preferred by farmers and the market. Of these, 13 have been released and 23 are in the pre-released stage. Intensification of scaling up and out of PVS in other locations in Mali, Niger and Nigeria in 2008 is ongoing.